2017
DOI: 10.1145/3140659.3080220
|View full text |Cite
|
Sign up to set email alerts
|

Non-Speculative Load-Load Reordering in TSO

Abstract: In Total Store Order memory consistency (TSO), loads can be speculatively reordered to improve performance. If a load-load reordering is seen by other cores, speculative loads must be squashed and re-executed. In architectures with an unordered interconnection network and directory coherence, this has been the established view for decades. We show, for the first time, that it is not necessary to squash and re-execute speculatively reordered loads in TSO when their reordering is seen. Instead, the reordering ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
1

Relationship

4
1

Authors

Journals

citations
Cited by 12 publications
(14 citation statements)
references
References 30 publications
0
14
0
Order By: Relevance
“…The insight of this study is that selective speculation, preserving or relaxing of one more conditions necessary for out-of-order commit, could lead to more efficient implementations. In fact, recent work [15,24] has shown that this might be the case for load instructions.…”
Section: Contributionmentioning
confidence: 99%
See 2 more Smart Citations
“…The insight of this study is that selective speculation, preserving or relaxing of one more conditions necessary for out-of-order commit, could lead to more efficient implementations. In fact, recent work [15,24] has shown that this might be the case for load instructions.…”
Section: Contributionmentioning
confidence: 99%
“…This is especially true if the potential benefits can be tapped with much more efficient and selective mechanisms to guarantee correctness, instead of bulk checkpointing and rollback. Already, such non-speculative mechanisms have been proposed [24].…”
Section: Analyzes Performedmentioning
confidence: 99%
See 1 more Smart Citation
“…In general, a deadlock avoidance mechanism cannot simply rely on increasing associativity (e.g., with the addition of a fully associative victim cache) as this only makes the deadlock more unlikely, but not impossible. Figure 8: Directory-eviction deadlock Note, here, that the resource conflict does not concern reads (loads), as the inability to evict means that read will be delayed until the atomic-group write completes-or the read will be performed as uncacheable [17].…”
Section: Resource-conflict Deadlocksmentioning
confidence: 99%
“…Our work is largely inspired by concepts introduced in the following works [10], [7], [5], [8], [25], [26], [6], [17]. We aim to show that store!store reordering in TSO, to the extent it is imposed by coalescing, can be achieved non speculatively.…”
Section: Related Workmentioning
confidence: 99%